ASSESSMENT OF JAK-STAT3 CELLULAR SIGNALING PATHWAY ACTIVITY USING MATHEMATICAL MODELLING OF TARGET GENE EXPRESSION - VELTER RICK; DOU MENG; VERHAEGH WILHELMUS F J; VAN DE STOLPE ANJA (2020)
The present invention relates to a computer-implemented method for inferring activity of a JAK-STAT3 cellular signaling pathway in a subject based on expression levels of three or more target genes ofthe JAK-STAT3 cellular signaling pathway measured in a sample of the subject. The present invention further relates to an apparatus, to a non-transitory storage medium, and to a computer program forinferring activity of a JAK- STAT3 cellular signaling pathway in a subject. The present invention further relates to a kit for measuring expression levels of three or more target genes of the JAK-STAT3 cellular signaling pathway in a sample of a subject, to a kit for inferring activity of a JAK-STAT3 cellular signaling pathway in a subject, and to the use of such kits in performing the method. 本发明涉及用于推测对象中JAK-STAT3细胞信号传导途径活性的计算机执行的方法，其中所述推测基于在对象样品中测量的JAK-STAT3细胞信号传导途径的三个或更多个靶基因的表达水平。本发明进一步涉及用于推测对象中JAK-STAT3细胞信号传导途径活性的装置、非暂时性存储介质和计算机程序。本发明进一步涉及用于测量对象样品中JAK-STAT3细胞信号传导途径的三个或更多个靶基因的表达水平的试剂盒，用于推测对象中JAK-STAT3细胞信号传导途径活性的试剂盒，